Nutrition education using eBook as an alternative to severely wasted prevention in underprivileged families during the COVID-19 pandemic at the Bambanglipuro Health Center - Johannis, Amanda Jelita Eka Riani (BKM Public Health and Community Medicine, 2021)
Objective: This study examines the severely wasted prevention eBook as an alternative to severely wasted prevention in underprivileged families during the COVID-19 pandemic at the Bambanglipuro Health Center. Content: The COVID-19 pandemic has hampered many health facilities, one of which is the Integrated Service Post. Active Integrated Service Post experience reporting problems because door-to-door implementation cannot be carried out in just one day. Meanwhile, the inactive Integrated Service Post makes it difficult to prevent severely wasted. Mothers do not realize that their child's nutritional status is deteriorating and must immediately seek treatment at the Public Health Center. This makes it difficult for mothers to get nutrition education, especially mothers from underprivileged families. Based on the above problems, the preventive steps taken began with online reporting of wasted and severely wasted toddlers using spreadsheets by cadres. Mothers and toddlers who are registered in online reporting must come to the Public Health Center for an integrated examination by doctors, midwives, nutritionists, and psychologists. However not all mothers accept the fact that their children are wasted or severely wasted. It is still a challenge for the Public Health Center to provide nutrition education to mothers. In the nutritionist section, an eBook on the prevention of severely wasted will be given. This eBook is expected to be an alternative so that nutrition education can still be carried out during the pandemic and can prevent severely wasted in underprivileged families. This is expected to help faster reporting and more accurate prevention of severely wasted in underprivileged families at the Bambanglipuro Health Center.